A CRITICAL REVIEW ON KARNINI YONIVYAPAD W.S.R. TO CERVICAL EROSION (AYUSHDHARA, 2018)
God has blessed the woman with most valuable gift of motherhood. A healthy woman can make healthy family and ultimately maker of healthy nation. Henceforth disease which causes physical or psychological concern to a woman should be immediately taken care of and so equally weighed in medical science. Cervical erosion is one of the most commonest gynaecological condition seen in OPDs. About 80% of women among her reproductive age group are suffering from this problem. Clinically it is defined as the development of red velvety area on the portio vaginalis around the external os. In Ayurvedic classical texts almost all the gynaecological disorders comes under the term 'Yonivyapad'.  All the classics have given the number of Yonivyapad as twenty. ‘Karnini yonivyapad’ is one among of them.  According to Acharya Charaka. Due to straining during labour in the absence of labour pains, the Vayu obstructed by  fetus, with holding Kapha and getting mixed with Rakta produces ‘Karnika’ in yoni, which obstructs the passage of Rakta (Raja). Due to presence of Karnika this condition is termed as ‘Karnini’. In the present article Ayurvedic review of  ‘Karnini Yonivyapad’ has been correlated with ‘Cervical erosion’ in Modern review  on the basis of morphological and physiological symptoms. Hence the description of ‘Karnini yonivyapad’ seems to be nearer to cervical erosion.